Service marketing and its impact on customer acquisition in a general services company, Lima, 2024 - Ramos-Malca, Viviana Elizabeth; Fernández-Bedoya, Víctor Hugo (LACCEI, 2024)
This study aimed to determine the impact of service marketing on customer acquisition in a general services company in Lima, Peru in 2024. Using a quantitative approach and an explanatory level, the incidence between the services marketing variable and customer acquisition was analysed. The sample consisted of 154 customers randomly selected from a population of 350 customers. The results show that service marketing has a positive and significant impact on customer acquisition, with a coefficient of determination of 76.73%. This suggests that service marketing is a key factor in attracting new customers and retaining existing ones. These findings indicate that the company should focus its efforts on developing effective service marketing strategies that comprehensively address the different aspects that impact on customer attraction and retention.